Production of esters fuel from pyrolysis oil using Al2(SO4)3 catalyst - Dan LUO; Shuqian XIA; Lixiao GUO; Jianrong HAN; Kewei JIANG; Quan[DK]’ai HAO; Jiao LI (Journal of Hebei University of Science and Technology, 2024)
In this paper, a way that using Al2[DK](SO4)3 catalyst to esterify those labile components (such as acids and sugars) in pyrolysis oil into fuel compounds was proposed considering that their presences were the main factor restricting pyrolysis oil's direct use as biofuel. Firstly, various metal sulfates catalysts were screened for producing ethyl levulinate from model compound levoglucosan or for producing ethyl acetate from model compound acetic acid. Secondly, the optimal reaction conditions were investigated for producing esters from the model mixture of levoglucosan and acetic acid over Al2[DK](SO4)3 catalyst. Thirdly, the feasibility of producing esters from the real pyrolysis oil over Al2[DK](SO4)3 catalyst under the optimum reaction conditions was validated. The results showed the formation of significant amounts of esters and acetals accompanying the loss of labile acids, sugars and aldehydes. The esters and acetals accounted for 39.5% of the total GC-MS chromatographic area of the esterified pyrolysis oil. This indicated that Al2[DK](SO4)3 could effectively catalyse the esterification of those labile components in pyrolysis oil to fuel compounds, which could provide reference for producing biofuels from pyrolysis oil..